Pharmacological effects of berberine and its derivatives: a patent update. (1st February 2016) - Jin, Yifeng; Khadka, Daulat B.; Cho, Won-Jea
ABSTRACT: Introduction : A number of plant-derived agents are used in many therapeutic areas. Berberine, an important protoberberine alkaloid, is present in a number of medicinal plants that have been widely used in traditional Chinese medicine for hundreds of years. Modern research has shown that berberine and its derivatives display several pharmacological effects through various mechanisms. Areas covered : This review discusses recent and mostly Chinese patents that report the synthesis of berberine, berberine derivatives and berberine salts, and methods of preparation for formulations (traditional Chinese medicine) containing herbal components rich in berberine, along with their applications. The review covers several therapeutic effects of berberine, its derivatives and pharmaceutical formulations against cancer, obesity, diabetes, inflammation, atherosclerosis, Alzheimer's disease, rheumatoid arthritis and cardiovascular diseases. In addition, the mechanisms underlying the pharmacological effects are discussed. Expert opinion : Modification of the functional groups of berberine has a significant effect on the pharmacological activity. However, studies on altering the atoms and size of the berberine skeleton are rare. Thus, it may be beneficial to initiate a drug development program focused on inserting heterocyclic rings of different sizes into berberine. Furthermore, structural modification to improve the safety, efficacy and selectivity is necessary to promote the use of berberine-based drugs in clinical settings.